2004
DOI: 10.1590/s1413-70542004000200019
|View full text |Cite
|
Sign up to set email alerts
|

Estudo das curvas de crescimento de cordeiros das raças santa inês e bergamácia considerando heterogeneidade de variâncias

Abstract: RESUMOFunções de crescimento não-lineares foram ajustados a dados de peso-idade de 40 cordeiros das raças Santa Inês e Bergamácia. Pelos testes de Hartley e de Bartlett, verificou-se que os dados apresentavam heterogeneidade de variâncias; em função disso, ajustaram-se as funções de crescimento pelo método dos quadrados mínimos ponderado pelo inverso da variância dos pesos a cada pesagem utilizando a opção WEIGTH do PROC MODEL (SAS INSTITUTE, 1996). As funções de crescimento foram comparadas pela interpretação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
20

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 3 publications
1
7
0
20
Order By: Relevance
“…Similar results were obtained in several studies that aimed to model the weight growth in relation to the length of animal species for commercial purposes: cattle and goats (FREITAS, 2007), sheep (GUEDES et al, 2004), shrimp (SILVA et al, 2007 and rabbit (FREITAS, 2007), for the Bertalanffy model, as presented R² greater than 0.99.…”
Section: Resultssupporting
confidence: 86%
“…Similar results were obtained in several studies that aimed to model the weight growth in relation to the length of animal species for commercial purposes: cattle and goats (FREITAS, 2007), sheep (GUEDES et al, 2004), shrimp (SILVA et al, 2007 and rabbit (FREITAS, 2007), for the Bertalanffy model, as presented R² greater than 0.99.…”
Section: Resultssupporting
confidence: 86%
“…PEREIRA et al (2005), in a study on the prediction of mineralized nitrogen in oxisol by using nonlinear models, incorporated the residual autocorrelation and found more precise parameters estimates. MAZZINI et al (2005) and MENDES et al (2008) analyzing growth of beef cattle, and GUEDES et al (2004) evaluating averaged data of lambs, observed a higher goodness of fit for models that incorporated autoregressive parameters. After implementation of appropriate corrective measures, a new estimation was done following a new residual diagnosis with normal distribution.…”
Section: Resultsmentioning
confidence: 99%
“…em estudos de regressão é comum admitir que os erros envolvidos no processo de estimação são independentes, o que não ocorre quando se trabalha com séries cronológicas (MORETIN e toloi, 2004). no caso de haver dependência entre os erros, as estimativas obtidas podem ser viesadas, com valores abaixo ou acima do verdadeiro valor do parâmetro (GUEDES et al, 2004;MAZZINI et al, 2005;PEREIRA et al, 2005). Em estudo do crescimento dos diâmetros longitudinal e transversal do fruto de coqueiro anão verde, Prado et al, (2013) obtiveram melhor ajuste dos modelos gompertz e logístico quando consideraram estrutura autocorrrelacionada de ordem 1 (AR1).…”
Section: Introductionunclassified